Leadership capabilities: Transforming your organisation for the digital age - LANGE, Katharina (Institutional Knowledge at Singapore Management University, 2019)
Leaders of large organisations need to strike a balance between speed and thoroughness, centralisation and decentralisation, and technology and the human touch.